2016
DOI: 10.1590/1678-457x.0074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adding flours from marolo fruit (Annona crassiflora Mart) and jerivá fruit (Syagrus romanzoffiana Cham Glassm) on the physicals and sensory characteristics of food bars

Abstract: The marolo (Annona crassiflora Mart.) and jerivá (Syagrus romanzoffiana Cham Glassm) fruits grow in the Cerrado biome, and have important sensory and nutritional characteristics. These fruits are eaten fresh or processed and embedded in ice cream, candy, juices, and liquors. However, their use is very limited and is localized exclusively to their native region. The aim of this study was to evaluate the use of these fruits in food consumer products to improve the nutritional patterns of consumers and extend kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
(15 reference statements)
0
1
0
1
Order By: Relevance
“…da Silva et al [44] found values ranging from 15.86 N to 17.87 N for shearing of food bars with marolo flour and jerivá, respectively. High values for food bar hardness measurement are not always associated with low acceptance of the product.…”
Section: Resultsmentioning
confidence: 99%
“…da Silva et al [44] found values ranging from 15.86 N to 17.87 N for shearing of food bars with marolo flour and jerivá, respectively. High values for food bar hardness measurement are not always associated with low acceptance of the product.…”
Section: Resultsmentioning
confidence: 99%
“…La aceptabilidad general para las muestras analizadas varió entre 5,0 a 7,9; denotándose el valor más alto en el tratamiento con contenido equitativo de copos de quinua y cáscara de piña en polvo (15,67%), seguido del tratamiento combinado con 20,90% de copos de quinua; 5,22 de cáscara de piña en polvo y 5,22 de salvado de avena (Cuadro 3). Otros investigadores reportan que los mayores resultados de aceptabilidad general utilizando una escala hedónica de 9 puntos en barras de cereales con fibra fueron de 7,25 [29]; 7,11 [34]; 6,9 [17] y 6,7 [5].…”
Section: Aceptabilidad Generalunclassified